INFORMATIONAL-METHODICAL SUPPORT OF THE COURSE «MATHEMATICAL LOGIC AND THEORY OF ALGORITHMS» - Sinko, Ю.І. (Journal of Information Technologies in Education (ITE), 2010)
In this article the basic principles of training technique of future teachers of mathematics to foundations of mathematical logic and theory of algorithms in the Kherson State University with the use of information technologies are examined. General description of functioning of the methodical system of learning of mathematical logic with the use of information technologies, in that variant, when information technologies are presented by the integrated specialized programmatic environment of the educational purpose «MatLog» is given.